Threshold Value of Blood Procalcitonin for the Diagnosis of Bacterial Meningitis in Children : A Systematic Review - Fransiska Christela; Benedicta .; Christopher . (Universitas Wijaya Kusuma Surabaya, 2025)
Introduction: Bacterial meningitis has a high mortality rate in children. Bacterial meningitis is diagnosed through medical history, physical and laboratory examinations, and mainly cerebrospinal fluid analysis through lumbar puncture (LP). The procedure on children might be challenging due to the multiple adverse effects; not all children comply with the procedure. There are studies with different blood biomarkers for the diagnosis because it is simple and less invasive in children. Objective: This review focused on the blood Procalcitonin (PCT) threshold value as a promising blood biomarker that might be useful for diagnosing bacterial meningitis in children. Methods: Literature search across 3 databases, Scopus, PubMed, and ScienceDirect, used PICO framework to structure the search, following the PRISMA standards. Of 759 articles, 11 articles met the criteria inclusion: children with meningitis under 18 years old, shows procalcitonin cut-off value and have lumbar puncture performed, sensitivity and specificity reported, in English. Exclusion criteria: studies of systematic reviews, meta-analyses, and literature reviews, as well as the value of blood procalcitonin as part of a scoring system or machine learning model.Results: The analysis of 11 articles reveals a blood PCT cut-off value of 0.2 to 10 ng/ml, with sensitivity ranging from 24% to 100% and specificity ranging from 63% to 94%. Conclusions: Blood PCT helps diagnose bacterial meningitis, especially for children who are not eligible for LP procedures. The blood PCT levels between 0.2 and 5 ng/mL showed a sensitivity of over 85%. The cut-off value with 100% sensitivity was found to be 2 ng/mL. A cut-off value exceeding 5 ng/mL demonstrated a specificity of over 90%.